2021
DOI: 10.3390/ijms222413318
|View full text |Cite
|
Sign up to set email alerts
|

Immunosenescence in Choroidal Neovascularization (CNV)—Transcriptional Profiling of Naïve and CNV-Associated Retinal Myeloid Cells during Aging

Abstract: Immunosenescence is considered a possible factor in the development of age-related macular degeneration and choroidal neovascularization (CNV). However, age-related changes of myeloid cells (MCs), such as microglia and macrophages, in the healthy retina or during CNV formation are ill-defined. In this study, Cx3cr1-positive MCs were isolated by fluorescence-activated cell sorting from six-week (young) and two-year-old (old) Cx3cr1GFP/+ mice, both during physiological aging and laser-induced CNV development. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
1
6
0
Order By: Relevance
“… 10 Accumulating evidence suggests that senescent macrophage/microglia, which might actually polarize toward the M2 phenotype, play a key role in abnormal angiogenesis. 11 , 12 However, the detailed mechanisms that regulate macrophage/microglia phenotypes and functions, particularly in aging-associated eye diseases, remain largely unclear.…”
mentioning
confidence: 99%
“… 10 Accumulating evidence suggests that senescent macrophage/microglia, which might actually polarize toward the M2 phenotype, play a key role in abnormal angiogenesis. 11 , 12 However, the detailed mechanisms that regulate macrophage/microglia phenotypes and functions, particularly in aging-associated eye diseases, remain largely unclear.…”
mentioning
confidence: 99%
“…Finally, for the comparison between human and murine microglia, mice aged at least 2 years were investigated resembling the average age of the patients that were included in this study. Since the age has a considerable influence on the expression profile of retinal microglia (18), discrepancies must be taken into account when investigating younger mice. A strength of this study is the use of fresh tissue, which was processed instantly after enucleation, allowing to preserve the RNA of sorted cells within four hours after surgery, which is significantly faster compared to other studies using post-mortem tissue with a time from death to preservation of 8 up to 17 h (36,38).…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional profile of murine retinal microglia previously published by our group (18) was re-analyzed and compared to data from human retinal microglia acquired in this study. In brief, immediately after enucleation, eyes were dissected in icecold PBS to isolate the retinae.…”
Section: Micementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the disease-associated induction of endothelial LRG1 expression, myeloid cells have also been found to express LRG1 in choroidal neovascularization. A recent study exploring the transcriptional profiling of immunosenescence in myeloid cells during the development of CNV showed that aged senescent myeloid cells of CNV-induced animals exhibited an upregulated angiogenic transcriptional profile with significantly elevated Lrg1 and Arg1 expression compared to young cells ( 115 ). This is the first study to provide evidence of upregulated Lrg1 expression in cells other than the endothelium contributing to choroidal neovascularization.…”
Section: Lrg1 and Vascular Pathology Of The Eyementioning
confidence: 99%